Use of iSpartan in teaching organic spectroscopy - Karatjas, A.G. (Journal of Chemical Education, 2014)
Spectroscopy is often one of the most difficult subjects in an organic chemistry course for students to master. One difficulty comes from relating peaks in a spectrum with structural features. For example, when teaching infrared spectroscopy, it is often difficult to connect the theory between bending and stretching vibrations to the actual peaks. iSpartan for the iOS platform allows this to be done easily without the high cost of the full Spartan software. © 2014 The American Chemical Society and Division of Chemical Education, Inc.
6 citations (Crossref) [2023-10-31]
Keywords: Computer-Based Learning; Organic Chemistry; Second-Year Undergraduate; Spectroscopy; dept.che; peer-reviewed